FIZIKA FANIDAN LABORATORIYA ISHLARINI BAJARISHDA DASTURIY TIZIMLARDAN FOYDALANSIH - Turekeev, X.S. (SCIENCE and SOCIETY, 2025)
This paper presents a method for determining the temperature dependence of sound speed in the laboratory. The graph of the dependence of the speed of sound on temperature is shown using the Maple program. The obtained results can be compared with the theoretically calculated values.